Primary intestinal lymphangiectasia (Waldmann's disease) - Vignes, Stéphane (BioMed Central, 2008)
Primary intestinal lymphangiectasia (PIL) is a rare disorder characterized by dilated intestinal lacteals resulting in lymph leakage into the small bowel lumen and responsible for protein-losing enteropathy leading to lymphopenia, hypoalbuminemia and hypogammaglobulinemia. PIL is generally diagnosed before 3 years of age but may be diagnosed in older patients. Prevalence is unknown. The main symptom is predominantly bilateral lower limb edema. Edema may be moderate to severe with anasarca and includes pleural effusion, pericarditis or chylous ascites. Fatigue, abdominal pain, weight loss, inability to gain weight, moderate diarrhea or fat-soluble vitamin deficiencies due to malabsorption may also be present. In some patients, limb lymphedema is associated with PIL and is difficult to distinguish lymphedema from edema. Exsudative enteropathy is confirmed by the elevated 24-h stool α1-antitrypsin clearance. Etiology remains unknown. Very rare familial cases of PIL have been reported. Diagnosis is confirmed by endoscopic observation of intestinal lymphangiectasia with the corresponding histology of intestinal biopsy specimens. Videocapsule endoscopy may be useful when endoscopic findings are not contributive. Differential diagnosis includes constrictive pericarditis, intestinal lymphoma, Whipple's disease, Crohn's disease, intestinal tuberculosis, sarcoidosis or systemic sclerosis. Several B-cell lymphomas confined to the gastrointestinal tract (stomach, jejunum, midgut, ileum) or with extra-intestinal localizations were reported in PIL patients. A low-fat diet associated with medium-chain triglyceride supplementation is the cornerstone of PIL medical management. The absence of fat in the diet prevents chyle engorgement of the intestinal lymphatic vessels thereby preventing their rupture with its ensuing lymph loss. Medium-chain triglycerides are absorbed directly into the portal venous circulation and avoid lacteal overloading. Other inconsistently effective treatments have been proposed for PIL patients, such as antiplasmin, octreotide or corticosteroids. Surgical small-bowel resection is useful in the rare cases with segmental and localized intestinal lymphangiectasia. The need for dietary control appears to be permanent, because clinical and biochemical findings reappear after low-fat diet withdrawal. PIL outcome may be severe even life-threatening when malignant complications or serous effusion(s) occur.